Strongly nonlinear degenerate elliptic equations with discontinuous coefficients. II - Bonafede, S. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We use energy methods to prove the existence and uniqueness of solutions of the Dirichlet problem for an elliptic nonlinear second-order equation of divergence form with a superlinear tem [i.e., g(x, u)=v(x) a(x)⋎u⋎ p−1u,p>1] in unbounded domains. Degeneracy in the ellipticity condition is allowed. Coefficients a i,j(x,r) may be discontinuous with respect to the variable r.